Innovative milieu and social capital - exploring conceptual complementarities (example of the Aachen region, Germany) - Martina Fromhold-Eisebith (European Regional Science Association (ERSA), 2002)
Since local systems of relationships (e.g. networks) have been recognized as crucial promoters of regional economic success and restructuring through industrial innovativeness, several concepts try to capture the essence of relevant developments. Much discussed notions such as industrial district, learning region, or innovative milieu each aim at highlighting certain facets of areas that prosper on the base of interacting agents. They represent specific, however complementary concepts, which are linked by the common central idea of the importance of intraregional collaboration. This paper picks up two approaches whose complementarities in explaining regional development and restructuring deserve to get further explored: innovative milieu and social capital. They both put into terms the benefits of trustful, information rich personal relationships in creating supportive externalities for innovative firms. In this regard the notion of social capital - originating from sociological discourse - has recently gained importance for explaining successful economic development as well. The following conceptual questions emerge and will be dealt with in the paper: In which ways can regional development theory profit by linking the milieu and social capital approaches? Are there important complementarities in connecting both concepts, or do we rather find redundancies as they both address the same categories of local interaction and must be considered kind of synonymous? The paper tries to explore these issues by combining theoretical considerations with the application to a case study. It first highlights major elements of both the concept of innovative milieus and the notion of social capital (in the context of regional economic development). The emphasis is put on deriving complementary aspects of both approaches: while the first one sets the spotlight on the qualities of heterogeneous networks of agents that creatively combine widely differing competencies, the second one rather relates to the collaboration externalities of more homogeneous groups of actors. It shall be shown that the connection of both concepts helps to better explain the role of personal and informal relationships of agents as promoters of innovation-based regional restructuring. The theoretical conclusions are then examplified by looking at the features and factors of industrial transformation of the German region of Aachen. Formerly an 'old industrialised' area based on textile and mining industries, Aachen has managed to successfully restructure its economy through the growing emergence of innovative, knowledge-intensive firms. This process, which has gained momentum since the mid 1980s, has its main foundations in formally and informally constructed systems of personal collaboration and mutual support. A closer look at the patterns of interaction reveals that this success can much better be explained when distinctions are drawn between milieu and social capital externalities.
Keywords: 330